Metastatic craniocervical hemangiopericytoma presenting with hydrocephalus and papilledema – Case review. (October 2018) - Kweh, Barry Ting Sheen; Pham, Chengde; McLean, Catriona; Tee, Jin Wee
Highlights: This is the first published case to our knowledge of recurrent craniocervical hemangiopericytoma with cerebellar metastases. Complete surgical resection confers greatest overall benefit but can be challenging in eloquent regions. Physician vigilance is required for surveillance due to the propensity of long term local recurrence or distant metastases. Abstract: Hemangiopericytomas are rare mesenchymal tumors with propensity to recur locally and metastasize. We report the unique case of a fifty-five-year-old male with recurrence of a previously resected craniocervical hemangiopericytoma presenting with obstructive hydrocephalus secondary to new metastatic cerebellar deposits. Emergent surgical resection of the cerebellar hemangiopericytomas was performed prior to adjuvant radiotherapy. Hemangiopericytomas are rare but important differentials for craniocervical junction lesions. Gross total resection remains the cornerstone of management with post-operative radiotherapy and chemotherapy as potential adjuncts. Tumors located in deep regions pose complex management challenges as safe maximal excision may be limited by proximal eloquent structures.